Product design and engineering : formulation of gels and pastes - Bröckel, Ulrich; Meier, Willi; Wagner, Gerhard (Wiley-VCH, 2013)
"Covering the whole value chain - from product requirements and properties via process technologies and equipment to real-world applications - this reference represents a comprehensive overview of the topic. The editors and majority of the authors are members of the European Federation of Chemical Engineering, with backgrounds from academia as well as industry. Therefore, this multifaceted area is highlighted from different angles: essential physico-chemical background, latest measurement and prediction techniques, and numerous applications from cosmetic up to food industry."--Resumé vydavatele
Keywords: chemické inženýrství; chemické výrobky; disperzní systémy; emulze; gely; tekutiny; reologie; vlastnosti materiálů; chemical engineering; chemical products; dispersive systems; emulsions; gels; liquids; rheology; materials properties; kolektivní monografie; elektronické knihy; collective monographs; electronic books